Invisible victims of non-ethical reporting on suicide in Serbia - Dokmanović Mirjana 0. (Temida)
The subject of this paper is the analysis of the way the daily printing in Serbia is engaged in the reporting on suicide and the level of respect of the Code of Ethics of Serbian Journalists. The aim of thee paper is to present and analyse the findings of the research on the manner of reporting on cases of suicide in electronic editions of eight daily newspapers in the period from 1st January to 30th September 2018. Both quantitative and qualitative analysis of the media content, including photographs and video footage was performed. The research findings showed that only two dailies out of eight fully followed the professional and ethical conduct for journalists. In total, 223 articles have been published about cases of suicide. Out of this number, the Code of Ethics has been violated in 147 articles (65.9%). In 40 articles media un-ethically reported on cases of suicide of children and minors. The most frequent methods of the Code of Ethics’ violations include: disrespect of dignity, privacy and grief of people who have experienced the death from suicide of a loved one, publishing photographs of the scene of a given suicide, and pictures of an individual who has died by suicide and of his/her family members, and using language which sensationalises suicide. Due to unethical reporting, members of the family of the persons who committed suicide have been exposed to additional trauma and stigmatization, thus becoming invisible victims of irresponsible media reporting. The analysis of the legal and institutional framework has shown that mechanisms for the protection of their right to privacy and dignity are in place. Beside court protection, the victims of non-ethical reporting may seek protection from the Press Council, an independent self-regulatory body that has been established for monitoring the observance of the Code of Ethics and solving complaints made by individuals and institutions related to media content. However, it has been found that the traumatised and stigmatised family members very rarely use these opportunities provided. The analysis of the complaint proceedings before the Press Complaints Commission from the beginning of its work in September 2011 to 2019 showed that only three persons filed complaints against media seeking protection of their right to privacy and dignity.